PENGARUH TINGKAT PENDIDIKAN, PAD, DAN UMK TERHADAP KESEMPATAN KERJA DAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI BALI - Giri, I Made Rama Stana Pramana; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044], 2022)
Economic growth usually followed a declining unemployment. Factors influence job opportunities and economic growth education level, PAD, and UMK. The purpose analyze (1) education level, PAD, and UMK on job opportunities in Bali Province. (2) level of education, PAD, and UMK and employment opportunities on economic growth. (3) effect level of education, PAD, and UMK on economic growth through employment opportunities. This study uses panel data of 90 observations. The analytical method used path analysis. The results (1) level of education and UMK don’t has effect on job opportunities in regency/city of Bali Province. PAD has a significant positive effect on district/city employment opportunities in the Province of Bali. (2) level of education and employment opportunities have a significant positive effect on the economic growth of the regency/city of Bali Province, while the UMK has a significant negative effect on economic growth and PAD has no significant effect on the economic growth of the regency/city of Bali Province. (3) Employment opportunities mediate the influence of PAD on economic growth. Meanwhile, job opportunities do not mediate the effect of education level and PAD on economic growth. Keywords: Education Level, PAD, UMK, Job Opportunities, Economic Growth